PENGARUH PENDIDIKAN KESEHATAN TENTANG VASEKTOMI TERHADAP PENGETAHUAN DAN MOTIVASI MENGGUNAKAN VASEKTOMI DI DUSUN JELOK DESA BEJI WONOSARI - As Ganda Prasetya; Melania Wahyuningsih; anita liliana (Universitas Respati Yogyakarta, 2020)
Background: The number of people who got a vasectomy in Indonesia is still low. The lack of knowledge is one of the factors that cause the low number of people who get a vasectomy. In order to increase the number of people who get a vasectomy, a health education about vasectomy is needed. Objective: To determine the influence of health education about vasectomy on the knowledge about and motivation to get a vasectomy. Methods: This is a quasi- experiment research with a one group pretest posttest design, the research samples were selected using a total sampling technique, the instruments used for this research were questionnaires, and the data collected were analyzed using Wilcoxon’s test and paired t-test. This research was conducted in Jelok hamlet, Beji village, with 31 fertile males involved as respondents. Results: Respondents’ knowledge score before health education was given showed a mean of 9, and after health education, the mean was 1.94. Motivation to get a vasectomy before health education was given showed a median score of 24, after health education was given, the median score was 26. Data analysis on knowledge about vasectomy using a paired t-test showed a p-value of 0.000. An analysis on motivation using Wilcoxon’s test showed a p-value of 0.003. Conclusion: There was a significant influence of health education about vasectomy on the knowledge about and motivation to get a vasectomy.